(untitled) (Scientific Journal of Research Studies in Future Management, 2025)
In recent decades, sustainable fiscal strategies have gained increasing attention as essential levers for reinforcing innovation ecosystems and advancing knowledge-driven economic structures. These frameworks seek to achieve harmony between economic expansion, fiscal stability, and systematic support for innovation, thereby laying the groundwork for sustainable progress. The present study, using a descriptive–analytical methodology, investigates the influence of sustainable financial policies on the commercialization of knowledge-based initiatives within Iran’s national economic context. Empirical data were compiled from reliable international and domestic institutions, including the World Bank, the OECD, and Iran’s Vice-Presidency for Science and Technology. The results suggest that employing sustainable fiscal instruments—such as green financing mechanisms, innovation-centered tax incentives, and long-term R&D investments—contributes meaningfully to improving innovation performance and enhancing the competitiveness of knowledge-based enterprises. Furthermore, the establishment of transparent and adaptive fiscal frameworks that integrate innovation impact assessments is of paramount importance. Overall, sustainable fiscal policy emerges not merely as a means of economic regulation but as a principal catalyst for innovation vitality and the long-term development of knowledge-oriented economies.